DO TOURNAMENT SCHEDULE AND SQUAD COMPOSITION INFLUENCE INJURY TYPES AND RATES IN INTERNATIONAL RUGBY?. Issue 7 (11th March 2014) - Mathema, P; Moore, I; Ranson, C
Abstract : Background: This report contrasts injury rates, types and potential risk factors between two equal length yet markedly different international rugby campaigns. Objective: To compare tournament injury problems and potential risk factors for single nation versus combined nation international rugby teams. Design: Details of all time-loss injuries, training and match exposure for the Wales Team during the 2013; 6 Nations, and British and Irish Lions (BIL) during the Australia tour. Analysis was based on consensus injury surveillance methods. Setting: International Rugby Union. Participants: All Wales (n=36) and 2013 BIL squad (n=45) players. Risk factor assessment: Contrasting injury exposure, rates and severity. MainoOutcome measurement: Training and match injury; exposure, incidence, (per 1000hours), prevalence (% of players unavailable) and days-lost per injury. Results: Wales played 5 matches and BIL 10 in a similar time period. 81% of Wales' squad players played in at least one match as compared to 98% of BIL. Wales had 28% more training hours exposure. Wales had a higher injury incidence/1000 hrs than BIL (total 27 vs. 18, match 260 vs. 90, training 5 vs. 4) and prevalence (15 vs. 10%), but fewer days-lost per injury (11 vs. 17). For Wales, 67% of the squad sustained injuries, with an average of 1.6 injuries per injured player whilst 54% of BIL sustained injuries (1.1 per injured player). Forty-seven percent of Wales players started in a match and half were replaced in at least one game as compared to 62% of BIL players and 92% being replaced. Of the match injuries, 81% of Wales' players, versus 56% BIL, completed the match. Conclusions: Higher injury rates for Wales may have been due to factors such as; lower substitution rates, greater starter match exposure and previously injured players returning to play in the same tournament.